Reproductive Futurism in Evangelical and Secular Environmental Politics - Bjork-James, Sophie (Journal for the study of religion, nature and culture, 2026)
This article explores the relationship between ideas about kinship and climate politics through the concept of reproductive futurism. Ideas about reproduction and future children define multiple sites of North American engagements with the climate crisis, where the human child comes to represent "a safe passage into the future" (Sheldon 2016). Even within efforts to address climate change, this framework limits ethical action to solely the human, foreclosing the possibility of new ethical frameworks. I begin with the anti-environmental politics of a white evangelical pro-life orientation, one where concern about abortion often serves to occlude care about the environment and the climate crisis. I then show how reproduction and environmental politics are often united in secular responses to the climate crisis through a focus on the figure of imagined future children. Included in this is a call for scholars of religion to explore the possibilities for convergences of secularism and religion.